Phenylmethimazole is a candidate drug for the treatment of severe forms of coronavirus disease 2019 (COVID-19) as well as other virus-induced "cytokines storm". (January 2021) - Giuliani, Cesidio; Bucci, Ines; Napolitano, Giorgio
Abstract: Severe forms of the Coronavirus disease 2019 (COVID-19) are characterized by an enhanced inflammatory syndrome called "cytokine storm" that produces an aberrant release of high amounts of cytokines, chemokines, and other proinflammatory mediators. The pathogenetic role of the "cytokine storm" has been confirmed by the efficacy of immunosuppressive drugs such as corticosteroids along with antiviral drugs in the treatment of the severe forms of this disease. Phenylmethimazole (C10) is a derivative of methimazole with anti-inflammatory properties. Studies performed both in vitro and in vivo have shown that C10 is able to block the production of multiple cytokines, chemokines, and other proinflammatory molecules involved in the pathogenesis of inflammation. Particularly, C10 is effective in reducing the increased secretion of cytokines in animal models of endotoxic shock. We hypothesize that these effects are not limited to the endotoxic shock, but can also be applied to any disease characterized by the presence of a "cytokine storm". Therefore, C10 may be a potential drug to be used alternatively or in association with the corticosteroids or other immunosuppressive agents in the severe forms of COVID-19 as well as other viral diseases that induce a "cytokine storm". Preclinical and clinical studies have to be performed to confirm this hypothesis.